The Implementation of Dhuha Prayer Habituation in Shaping Students’ Religious Character at SMP Islam Al Azhar 52 Bengkulu City - Adinda Thamrin; Elpritahayati; Yuni Faddhillah S; Hengki Satrisno; Dalima Septiria (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This study aims to examine the implementation of Dhuha prayer habituation in shaping students’ religious character at SMP Islam Al Azhar 52 Bengkulu City. The research focuses on the implementation process, the role of habituation in developing religious character, and the supporting and inhibiting factors encountered during the program. A qualitative research approach with a descriptive design was employed to obtain an in-depth understanding of the phenomenon. Data were collected through observations, interviews, and documentation involving teachers and students. The findings indicate that Dhuha prayer habituation is implemented in a structured and consistent manner as part of the school’s daily religious activities. The program contributes positively to the development of students’ religious awareness, discipline, responsibility, and sincerity in worship. Supporting factors include strong institutional commitment, active teacher involvement, and adequate facilities, while inhibiting factors involve differences in students’ motivation, time constraints, and environmental conditions. Overall, Dhuha prayer habituation functions as an effective strategy for religious character education at the secondary school level.